2016
DOI: 10.1017/psrm.2015.78
|View full text |Cite
|
Sign up to set email alerts
|

Linking Party Preferences and the Composition of Government: A New Standard for Evaluating the Performance of Electoral Democracy

Abstract: We propose a new standard for evaluating the performance of electoral democracies: the correspondence between citizens’ party preferences and the party composition of governments that are formed after elections. We develop three criteria for assessing such correspondence: the proportion of citizens whose most preferred party is in government, whether the party that is most liked overall is in government, and how much more positively governing parties are rated than non-governing parties. We pay particular atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 43 publications
0
26
0
1
Order By: Relevance
“…While a proportional system with coalition governments should increase the proportion of citizens whose preferred party enters government, that proportion should still be limited. As noted, Blais, Guntermann and Bodet () found that, on average, 50.2% of citizens find their preferred party in government in proportional systems. Table shows the proportions of Canadians whose preferred party was in cabinet in actual governments as well as in simulated single‐party and coalition governments.…”
Section: Resultsmentioning
confidence: 84%
See 4 more Smart Citations
“…While a proportional system with coalition governments should increase the proportion of citizens whose preferred party enters government, that proportion should still be limited. As noted, Blais, Guntermann and Bodet () found that, on average, 50.2% of citizens find their preferred party in government in proportional systems. Table shows the proportions of Canadians whose preferred party was in cabinet in actual governments as well as in simulated single‐party and coalition governments.…”
Section: Resultsmentioning
confidence: 84%
“…While evidence suggests that electoral systems make little difference to how well citizens’ ideological preferences are reflected in government, a recent study finds that electoral systems do matter to another aspect of citizens’ preferences. Blais, Guntermann and Bodet () considered how well citizens’ party preferences are reflected in government. This approach to evaluating representation considers the extent to which parties citizens like more are better represented in government, while those they like less are less well represented in cabinet.…”
Section: Why Multi‐party Government Does Not Influence Ideological Comentioning
confidence: 99%
See 3 more Smart Citations